Theoretical analysis on strontium-tellurium content dependencies of defect structures and spin Hamiltonian parameters for strontium-tellurium titanium borate glasses with V2O5 dopants. (18th April 2022) - Zhou, Hong-Fei; Dong, Hui-Ning; Liu, Xu-Sheng
Abstract : Based on the perturbation formulae of the spin Hamiltonian parameters (SHPs) for a tetragonally compressed octahedral 3d 1 cluster, the defect structures and SHPs of V 4+ in strontium-tellurium borate ((30-x)SrO-xTeO2 -10TiO2 -58B2 O3 -2V2 O5 at distinct TeO2 contents x = 1, 2, 3, 4 and 5 mol %) glasses are systematically investigated. The involved model quantities (i.e. covalent factor N, tetragonal compression ratio τ, core polarization constant κ and reduction factor H ) at various x reasonably reproduce the experimental SHPs, and these quantities are further fitted with uniform Fourier-type content functions (FTCF) with merely three adjusted parameters. The different content fluctuations of these quantities are ascribed to content declines of the strong network modifier SrO and hence the modulations in local tetragonal compression, system compactness and electron cloud distribution near vanadium in the glass network. GRAPHICAL ABSTRACT: UF0001